2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332869
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic imaging of speech and swallowing with MRI

Abstract: Dynamic imaging with MRI holds great promise for visualizing soft tissue structures in the oropharyngeal region during speech and swallowing studies. However, MRI suffers from historically slow acquisition speed and sensitivity to significant magnetic susceptibility differences in this region. In this work, we describe our efforts in creating high temporal resolution, serial acquisitions of the muscles of the oropharyngeal region. We describe our imaging approach that leads to acquisition rates of up to 21 fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…The present study demonstrates the importance of an additional image plane for static and dynamic assessments, that is, the oblique coronal image plane. Bae et al (2011) and Sutton et al (2009) demonstrated a similar high temporal, serial acquisition during speech production; however, data were obtained only in the midsagittal image plane. Although the imaging rate was high (21 fps), both studies used a head-only MRI system that is typically designed for brain imaging.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study demonstrates the importance of an additional image plane for static and dynamic assessments, that is, the oblique coronal image plane. Bae et al (2011) and Sutton et al (2009) demonstrated a similar high temporal, serial acquisition during speech production; however, data were obtained only in the midsagittal image plane. Although the imaging rate was high (21 fps), both studies used a head-only MRI system that is typically designed for brain imaging.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, the images in the native frame rate (15.8 fps) could be interpolated to the desired output rate, but this would result in significant blurring of information across time. The sliding-window reconstruction process minimizes redundant information in adjacent time points and minimizes temporal blurring (Sutton et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…We created a 3D finite element model of the VP mechanism based on static MRI scans of a 20-year-old Japanese male subject with healthy VP anatomy and compared velum deformations with dynamic MRI scans 1921 . The model components included the velum, the PPW, the LVP, and the MU (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Upright MRI scanners have been proposed by some [26]; however, these are not as readily available as traditional scanners requiring a prone or supine position. Utilization of highspeed imaging sequences have enabled near real-time visualization of the process of swallowing [27][28][29]. It is important to have an understanding of the effects of gravity on the process of swallowing so that findings from such data sets (e.g., supine MRI data and upright swallowing studies) can be used interchangeably.…”
Section: Limitations Of the Study And Future Researchmentioning
confidence: 99%